Classification of Smart Card Operating Systems - Reza Asgari; Reza Ebrahimi Atani (Universitas Sriwijaya, 2014)
Today, smart cards are widely used in variety of applications of human life.The nature of these cards depends on theirs operating system, in other words the operating system determines that card can be used in what field. Hardware development on the one hand and increasing use of smart cards on the other, have led to that the operating systems have progressed dramatically.Moving from special-purpose operating systems with single application into multi-purpose operating systems with open architecture, is proof of claim.Increase the number of operating systems and variety of their applications, caused that the need to categorize and classify operating systems be felt more than ever.Smart card operating systems can be categorized based on different parameters such as file management, applications management, and historical generations. In this paper we will discussion about smart card operating systems and their classification based on these parameters.